Comparative genomic analysis of ten Elizabethkingia anophelis isolated from clinical patients in China - Fei Wu; Yan Wu; Miaomiao Zhang; Lijun Tian; Xue Li; Xi Luo; Yiquan Zhang; Renfei Lu (Microbiology Spectrum)
ABSTRACT Elizabethkingia anophelis is an emerging pathogen that causes life-threatening infections in neonates and immunocompromised patients. In this study, we performed next-generation sequencing (NGS) to characterize 10 E. anophelis strains isolated from clinical patients in Nantong, China. Core, accessory, and unique genomes were composed of 2,891, 1,633, and 498 genes, respectively. Based on genetic screening for antimicrobial resistance genes (AMRs), all E. anophelis strains carried the same AMRs, including blaB, blaCME, and blaGOB. The virulence factors (VFs) in the 10 strains were classified into 13 functional categories, and the differences between strains were mainly in immune modulation and nutritional/metabolic factor. We further analyzed the genomic features of one of ten strains, NT06 strain. The capsule type of NT06 was X, which is rare among E. anophelis strains. Based on comparative analyses, we first found that NT06 carried the YclNOPQ-like operon, which is the complete transporter for petrobactin, to acquire iron. The genomic features are important for further investigations of epidemiology, resistance, virulence, and to identify appropriate treatments.IMPORTANCEElizabethkingia anophelis strains are opportunistic pathogens causing meningitis, bloodstream infections, and endophthalmitis in vulnerable populations. There is a lack of knowledge of the genetic diversity, presence of antimicrobial resistance genes (AMRs), and virulence factors (VFs) in E. anophelis isolated from clinical patients in China. Based on next-generation sequencing (NGS) and comparative genomic analyses, we determined the genomic features, phylogeny, and diversity of E. anophelis strains isolated from patients and identified a large accessory genome, intrinsic AMRs, and variable VFs. Based on comparative analyses, we identified a key strain, NT06, that carried a unique capsule type of X and the siderophore-mediated iron acquisition system (yclNOPQ-like genes). These findings advance our understanding of the genomic plasticity, evolution, and pathogenicity determinants of E. anophelis.